ANALYSIS OF IMAM SYAFI'I OPINION ON TALAK BA'IN QUBRA AND ITS IMPLEMENTATION IN THE LAW. NO. 1 OF 1974 - Atambua Timur, Zainuddin Assiyadi (STAI Darul Kamal NW Kembang Kerang, 2024)
This article discusses the conflict between Imam Syafi'i's opinion and the Law. No. 1 of 1974 concerning triple talaq. Imam Syafi'i is of the opinion that triple talaq cannot be referred to again, whereas the law and KHI provide confirmation that divorce only occurs in front of a court hearing. In conducting this research, the author used a type of library research where the types and sources of data used were primary and secondary. Primary data consists of scientific work that is directly related to the main research theme, while secondary data is supporting data. After carrying out a long process, the results of this research show that Imam Syafi'i's opinion regarding Ba'in Qubro talak is not relevant for use in Indonesia, because in reality its implementation uses the basis of law. No. 1 of 1974 and the Compilation of Islamic Law, which clearly explains that there is no legal power for people who have triple divorced outside of court, even though they have been triple divorced, there will still be mediation efforts to reconcile, according to the orders of the Law. No. 1 of 2016 concerning mediation and the divorce pledge only exists before the court.